Modification of two-dimensional Ti0. 87O2 nanosheet on diaphragm and application of two-dimensional Ti0. 87O2 nanosheet in lithium metal battery
By modifying the separator with two-dimensional Ti0.87O2 nanosheets, a negative charge atomic-level ion selective transmission channel is constructed, which solves the problems of high tortuosity of lithium ion transmission and high interface impedance in lithium metal batteries, and improves the cyclic stability and energy of the battery Density, suitable for mass production.
Patent Information
- Application Number
- CN202411290832.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
AI Technical Summary
Lithium ions in lithium metal batteries have high tortuosity and high interface impedance in the ion channels formed by nanosheets, resulting in uneven deposition of lithium metal and low Coulomb efficiency. The modification of existing three-dimensional materials leads to low energy density of the battery and high aspect ratio two-dimensional materials. The modified ion transmission channel is long, the battery has poor dynamic performance, and the modified material is high and the preparation process is complex, which is not conducive to large-scale industrial production.
The modification of the separator by using two-dimensional Ti0.87O2 nanosheets, the liquid phase of the layered titanate parent structure was peeled into a single-layer titanium dioxide nanosheet, mixed with polyvinylidene fluoride and solvent, and scraper coating was performed on the surface of the PE separator. , a titanium oxide modified composite separator with ultra-thin high aspect ratio cation defects is formed, and a negatively charged atomic-level ion selective transmission channel is constructed to achieve uniform transmission of lithium ions.
It realizes uniform transmission of lithium ions, improves the cycle stability and energy density of lithium metal batteries, reduces the cost of modification materials, simplifies the preparation process, is suitable for large-scale production, and enhances the strength of the diaphragm and the dynamic performance of the battery.
Smart Images

Figure CN119133772A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high specific energy lithium metal batteries, in particular to two-dimensional Ti 0.87 Modification of separators by O2 nanosheets and their application in lithium metal batteries. Background Art
[0002] The rapid development of mobile electronic devices and electric vehicles has led to an increasing demand for high energy density power batteries. Metallic lithium has a high theoretical capacity (3860mAh g -1 ) and the lowest reduction potential (-3.04 V compared to the standard hydrogen electrode) are considered to be the ideal negative electrode for high energy density rechargeable batteries. However, the practical application of lithium metal anode (LMA) is seriously hindered by the uncontrollable growth of lithium dendrites. Specifically, the solid electrolyte interface (SEI) is constantly broken / repaired, and due to the high reactivity of lithium and electrolyte, disordered lithium dendrites continue to react with the electrolyte, accompanied by the formation of irreversible "dead lithium", and the electrolyte and lithium metal are constantly consumed, resulting in severe capacity loss and low coulombic efficiency, which may even cause some safety hazards.
[0003] According to Chazalviel theory, when Li + When the concentration of lithium decreases to zero near the LMA surface, lithium dendrites begin to nucleate, and this time is the Sand time. The starting nucleation time of lithium dendrites is related to the Li + Concentration and Li + The number of transfers (t Li+ ) is highly correlated. By accelerating the transport of lithium ions and increasing the Li+ transfer number (t Li+ ) to reduce the concentration gradient of lithium ions can delay the Sand time, so that lithium can be deposited uniformly and densely. + The surface modification of the separator can form a uniform and selective transmission channel for lithium ions on the surface of lithium metal, realize the uniform and dense deposition of lithium, thereby inhibiting the formation of lithium dendrites and inhibiting the reaction of lithium with electrolyte solvents. In addition, compared with the direct modification of lithium metal electrodes, this modification strategy has low environmental requirements and is more conducive to large-scale practical applications, providing a promising path for the large-scale production and industrial application of high-energy-density rechargeable batteries. So far, a large number of materials have been used to regulate the transmission of ions through the separator, such as inorganic materials, carbon materials, polymer materials, etc. However, these functional materials always need to be coated with a thicker thickness to completely cover the separator, which leads to a higher overall mass of the battery and seriously sacrifices the energy density of the battery. Therefore, the modified layer on the surface of the separator should not only selectively promote the uniform transmission of lithium ions, but also be as light and thin as possible, so as not to reduce the energy density of the power battery.
[0004] Two-dimensional (2D) atomically thin materials, including fluorinated graphene nanosheets (GFN), graphene oxide (GO), BN, SnS2, MXene, and MoS2, are considered to be very ideal separator modification materials due to their high aspect ratio. However, in densely stacked layer-by-layer assembled 2D materials, lithium ions can only be transported through the ion transport channels formed by the gaps between nanosheets. This ion channel has a high tortuosity, making Li + The transport distance is long, resulting in poor battery kinetics and high interfacial impedance of the electrode. 2D nanosheets with atomic-scale cation defects can produce more Li when assembled layer by layer. + This negatively charged ion transport channel can selectively promote Li + transport and achieve uniform Li at the atomic scale + Flux distribution, which can break the trade-off between ion selectivity and conductivity, while enhancing the strength of the separator without sacrificing battery energy density. However, there are still the following problems: lithium metal is deposited unevenly during the cycle, and the cycle coulomb efficiency of lithium dendrite generation is low; the high quality or high thickness of the existing three-dimensional material modified separator leads to low battery energy density; the high aspect ratio two-dimensional material modified separator has long ion transmission channels, slow ion diffusion transmission, and poor battery kinetic performance; the cost of modified materials is high, and the preparation process is complicated, which is not conducive to practical application and industrial large-scale production; the existing methods for modifying lithium metal negative electrodes have strict requirements on environmental humidity and other conditions, which is not conducive to industrial large-scale production and application. Summary of the invention
[0005] The object of the present invention is to provide a two-dimensional Ti 0.87 The modification of O2 nanosheets on the diaphragm and its application in lithium metal batteries are used to solve the problems of high tortuosity and high interface impedance of lithium ions in the ion channels formed by current nanosheets.
[0006] To achieve the above object, the present invention provides a two-dimensional Ti 0.87 Modification of separators by O2 nanosheets and their application in lithium metal batteries by liquid phase exfoliation of the layered titanate matrix structure into single-layer components Ti 0.87 O2 0.52- The titanium dioxide nanosheets are uniformly mixed with a binder, polyvinylidene fluoride, and a solvent, NMP, and then coated on the surface of the PE diaphragm by a doctor blade to obtain a titanium dioxide-modified composite diaphragm Ti 0.87 O2@PE, using Ti 0.87 O2@PE separator, assembled into button cells and soft-pack batteries.
[0007] The Ti 0.87The specific synthesis method of O2 nanosheets is as follows:
[0008] K2CO3, Li2CO3 and anatase TiO2 are mixed and ground to form a uniform precursor powder;
[0009] The precursor powder is calcined to obtain a layered titanate matrix K 0.8 Ti 1.73 Li 0.27 O4; after cooling to room temperature, the layered titanate was protonated by stirring in 0.5 M HCl solution for 10 min-2 d;
[0010] Protonated titanate H 1.07 Ti 1.73 The O4·H2O was washed with deionized water to a neutral pH, collected by filtration, and dried under vacuum at room temperature;
[0011] Stirring proton titanate in 0.01-0.02 M tetrabutylammonium hydroxide aqueous solution, a stable monolayer Ti 0.87 O2 0.52- Nanosheet suspension;
[0012] The obtained suspension is centrifuged at a rotation speed of 2000-5000 rpm, the supernatant is collected and freeze-dried to obtain cation defect single-layer nanosheet powder for further use.
[0013] Preferably, in the above two-dimensional Ti 0.87 Modification of the diaphragm by O2 nanosheets and its application in lithium metal batteries. When preparing the precursor powder, K2CO3 can be replaced by Cs2CO3, and the molar ratio of K2CO3, Li2CO3 and anatase TiO2 is 0.4:0.14:1.73.
[0014] Preferably, in the above two-dimensional Ti 0.87 The modification of the diaphragm by O2 nanosheets and its application in lithium metal batteries, the calcination conditions when the precursor powder is calcined are as follows: calcination at 800-1150°C for 10-24h.
[0015] Preferably, in the above two-dimensional Ti 0.87 Modification of the separator by O2 nanosheets and its application in lithium metal batteries, proton titanate was stirred in 0.01-0.02M tetrabutylammonium hydroxide aqueous solution for 5-14 days.
[0016] Preferably, in the above two-dimensional Ti 0.87 Modification of the diaphragm by O2 nanosheets and its application in lithium metal batteries. The modification process of the diaphragm by the nanosheets prepared above is as follows:
[0017] Adding titanium oxide nanosheets in an amount of 10-100 mg / mL into the NMP solution, and ultrasonicating to uniformly disperse the titanium oxide nanosheets in the NMP solvent;
[0018] Add polyvinylidene fluoride binder powder to the above mixed solution and stir for 2-7 hours to obtain a slurry;
[0019] After obtaining the slurry, the slurry is placed in a vacuum oven for vacuum defoaming, and an appropriate amount of the slurry is placed on the surface of the PE diaphragm for scraper coating. After coating, the diaphragm is placed in a vacuum oven and dried at 30-60°C to obtain a titanium oxide modified composite diaphragm Ti 0.87 O2@PE.
[0020] Preferably, in the above two-dimensional Ti 0.87 Modification of the separator by O2 nanosheets and its application in lithium metal batteries, the ultrasonic time is 30 minutes to 1 hour.
[0021] Preferably, in the above two-dimensional Ti 0.87 The modification of the diaphragm by O2 nanosheets and its application in lithium metal batteries, the mixed solution is added to the polyvinylidene fluoride solution in a ratio of titanium oxide: polyvinylidene fluoride = 3:1-1:4.
[0022] Preferably, in the above two-dimensional Ti 0.87 Modification of the diaphragm by O2 nanosheets and its application in lithium metal batteries. The application method of the diaphragm in lithium batteries is as follows:
[0023] Adopt Ti 0.87 O2@PE separator, assembled into button cells and soft-pack cells. All button cells are assembled in a glove box filled with argon, and all soft-pack cells are assembled in a dry room by a semi-automated battery production line.
[0024] Preferably, in the above two-dimensional Ti 0.87 Modification of diaphragms by O2 nanosheets and their application in lithium metal batteries. The conditions in the glove box are: H2O<0.1ppm, O2<0.1ppm, and the conditions in the dry room are: relative humidity 0.1%, dew point below -40°C, and a constant temperature of 25°C.
[0025] Therefore, the present invention adopts the above two-dimensional Ti 0.87 The modification of O2 nanosheets on the diaphragm and its application in lithium metal batteries realizes the simple and low-cost liquid phase exfoliation preparation of ultra-thin, high aspect ratio titanium oxide nanosheets containing cation defects; a simple scraping and coating method is used to modify the diaphragm to achieve ultra-thin, ultra-light, simple and large-scale modification of the lithium metal negative electrode in a natural environment; the modified layer two-dimensional materials are assembled layer by layer to construct negatively charged atomic-level ion selective transmission channels, and the ion transmission selectivity is achieved by the charge and steric effects, and the uniform transmission of lithium ions is achieved by multiple channels.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The two-dimensional Ti 0.87 Modification of the separator by O2 nanosheets and its application in lithium metal batteries Schematic diagram of the preparation process of titanium oxide nanosheets in the embodiment;
[0028] Figure 2 The two-dimensional Ti 0.87 Modification of the separator by O2 nanosheets and their application in lithium metal batteries; Ultra-thin cation vacancy defect nanosheets morphology and structural characterization results;
[0029] Figure 3 The two-dimensional Ti 0.87 Modification of separator by O2 nanosheets and its application in lithium metal batteries 0.87 Zeta potential spectrum of O2;
[0030] Figure 4 The two-dimensional Ti 0.87 Modification of separator by O2 nanosheets and its application in lithium metal batteries 0.87 Characterization diagram of O2@PE separator;
[0031] Figure 5 The two-dimensional Ti 0.87 Modification of separators by O2 nanosheets and their application in lithium metal batteries 0.87 Half-cell performance diagram of the separator modified with O2@PE ratio;
[0032] Figure 6 The two-dimensional Ti 0.87 Modification of separator by O2 nanosheets and its application in lithium metal batteries 0.87 Schematic diagram and morphology of half-cell deposition of O2@PE separator (cd) and PE (ab);
[0033] Figure 7 The two-dimensional Ti 0.87 Modification of separator by O2 nanosheets and its application in lithium metal batteries 0.87 XPS curves of symmetric batteries of O2@PE membrane and PE membrane after 40 cycles;
[0034] Figure 8 The two-dimensional Ti 0.87 Modification of separator by O2 nanosheets and its application in lithium metal batteries0.87 Symmetrical cells of O2@PE membrane and PE membrane at 1 mA / cm 2 1mAh / cm 2 Conditional cycle curve diagram;
[0035] Fig. 9 The two-dimensional Ti 0.87 Modification of separator by O2 nanosheets and its application in lithium metal batteries 0.87 LFP full battery cycle performance diagram of O2@PE separator and PE separator;
[0036] Fig.10 The two-dimensional Ti 0.87 Modification of separator by O2 nanosheets and its application in lithium metal batteries 0.87 811 full cell performance diagram of O2@PE separator and PE separator;
[0037] Fig.11 The two-dimensional Ti 0.87 Modification of separator by O2 nanosheets and its application in lithium metal batteries 0.87 Performance diagram of 811 soft-pack batteries with O2@PE separator and PE separator. DETAILED DESCRIPTION
[0038] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.
[0040] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.
[0041] The present invention provides a two-dimensional Ti 0.87 Modification of separators by O2 nanosheets and their application in lithium metal batteries by liquid phase exfoliation of the layered titanate matrix structure into single-layer components Ti 0.87 O2 0.52- The titanium dioxide nanosheets are uniformly mixed with a binder, polyvinylidene fluoride, and a solvent, NMP, and then coated on the surface of the PE diaphragm by a doctor blade to obtain a titanium dioxide-modified composite diaphragm Ti 0.87 O2@PE, using Ti 0.87 O2@PE separator, assembled into button cells and soft-pack batteries.
[0042] The Ti 0.87 The specific synthesis method of O2 nanosheets is as follows:
[0043] K2CO3, Li2CO3 and anatase TiO2 are mixed and ground to form a uniform precursor powder; wherein K2CO3 can be replaced by Cs2CO3, and the molar ratio of K2CO3, Li2CO3 and anatase TiO2 is 0.4:0.14:1.73.
[0044] The precursor powder is calcined to obtain a layered titanate matrix K 0.8 Ti 1.73 Li 0.27 O4; after cooling to room temperature, stirring in 0.5M HCl solution for 10min-2d to achieve protonation of the layered titanate; when the precursor powder is calcined, the calcination conditions are calcined at 800-1150°C for 10-24h.
[0045] Protonated titanate H 1.07 Ti 1.73 The O4·H2O was washed with deionized water to a neutral pH, collected by filtration, and dried under vacuum at room temperature;
[0046] Stirring proton titanate in 0.01-0.02 M tetrabutylammonium hydroxide aqueous solution, a stable monolayer Ti 0.87 O2 0.52- Nanosheet suspension: Proton titanate is stirred in 0.01-0.02M tetrabutylammonium hydroxide aqueous solution for 5-14 days.
[0047] The obtained suspension is centrifuged at a rotation speed of 2000-5000 rpm, the supernatant is collected and freeze-dried to obtain cation defect single-layer nanosheet powder for further use.
[0048] like Figure 2 As shown in 0.87 TEM images of O2 nanosheets, b is Ti 0.87 AFM image of O2 nanosheets, c is Ti0.87 HAADF-STEM image of O2 nanosheets; d is Ti 0.87 NMR spectrum of O2. It can be seen that ultrathin Ti 0.87 The O2 two-dimensional material is only 0.78nm thick and contains cation defects in the sample.
[0049] like Figure 3 As shown in Figure 3 Ti 0.87 Zeta potential spectrum of O2 proves that the nanosheets have negative charge.
[0050] The modification process of the diaphragm by the nanosheets prepared above is as follows:
[0051] Adding titanium oxide nanosheets in an amount of 10-100 mg / mL into the NMP solution, and ultrasonicating for 30 minutes to 1 hour to uniformly disperse the titanium oxide nanosheets in the NMP solvent;
[0052] Add polyvinylidene fluoride binder powder to the above mixed solution and stir for 2-7 hours to obtain slurry; when the mixed solution is added to the polyvinylidene fluoride solution, the ratio of titanium oxide: polyvinylidene fluoride is 3:1-1:4.
[0053] After obtaining the slurry, the slurry is placed in a vacuum oven for vacuum defoaming, and an appropriate amount of the slurry is placed on the surface of the PE diaphragm for scraper coating. After coating, the diaphragm is placed in a vacuum oven and dried at 30-60°C to obtain a titanium oxide modified composite diaphragm Ti 0.87 O2@PE.
[0054] like Figure 4 The figure shows the characterization of the prepared titanium oxide modified composite membrane, where a is Ti 0.87 The cross-sectional SEM image of the O2@PE separator shows that the nanosheets are arranged in horizontal stacks.
[0055] b, c are Ti 0.87 The GI-WAXS image (c) and I-χ pole figure fitting curve of the O2@PE diaphragm prove that the nanosheets are stacked horizontally on the surface of the diaphragm with a high degree of orientation and a Hallman orientation factor of 0.9.
[0056] d is Ti 0.87 AFM images of the O2@PE membrane surface show that Ti 0.87 The Young's modulus of the O2@PE separator is as high as 8.3 GPa, and it has good mechanical properties.
[0057] e is Ti 0.87 Contact angle images of O2@PE and PE separators, showing Ti 0.87 O2@PE separator has good wettability to electrolyte.
[0058] The application method of the above-mentioned diaphragm in lithium battery is as follows:
[0059] Adopt Ti 0.87 O2@PE separator, assembled into button cells and soft-pack cells. All button cells are assembled in a glove box filled with argon, and all soft-pack cells are assembled in a dry room by a semi-automated battery production line.
[0060] The conditions in the glove box are: H2O<0.1ppm, O2<0.1ppm, and the conditions in the dry room are: relative humidity 0.1%, dew point below -40°C, and constant temperature of 25°C.
[0061] In two-dimensional Ti 0.87 In the embodiment of the application of the separator modified by O2 nanosheets in lithium metal batteries, Ti 0.87 O2@PE membrane, and unmodified commercial PE membrane as a control example, were assembled into button cells and soft-pack cells for battery performance testing. All button cells were assembled in a glove box filled with argon (H2O <0.1ppm, O2 <0.1ppm), and all soft-pack cells were assembled in a dry room (relative humidity 0.1%, dew point below -40°C, constant temperature at 25°C) by a semi-automated battery production line.
[0062] Example 1
[0063] Li||Cu half-cell: 450μm lithium foil, Ti 0.87 O2@PE diaphragm or PE diaphragm and copper foil form Li||Cu half-cells to study the deposition morphology of lithium with different capacities and test their coulombic efficiency. 30μL electrolyte is added to each Li||Cu half-cell. Constant current experiments are performed on a Neware multi-channel battery tester.
[0064] Cyclic test conditions: first at 0.05 mA cm -2 The current density was activated for five cycles in the voltage range of 0.01-1 V, and then at 2 mA cm -2 Lithium deposition was carried out for 0.5 h at a current density of , and then the voltage was increased to 1 V for lithium desorption, and a cyclic test was carried out with this as the cycle.
[0065] Deposition test conditions: first at 0.05 mA cm -2 The current density was activated for five cycles in the voltage range of 0.01-1 V, and then at 1 mA cm -2 Lithium deposition was carried out for 5 h at a current density of .
[0066] like Figure 5 As shown, Figure 5 For different Ti 0.87The half-cell performance diagram of the O2@PE ratio-modified diaphragm shows that 60 mg / ml is the optimal concentration for modification.
[0067] Figure 6 Ti 0.87 Schematic diagram and morphology of half-cell deposition of O2@PE separator (cd) and PE (ab). It can be seen that the Ti 0.87 The lithium metal deposition of O2@PE separator is more uniform and dense.
[0068] Example 2
[0069] Li||Li symmetric battery: two identical lithium sheets (450 μm) are used as the positive and negative electrodes of the battery, respectively. 0.87 O2@PE membrane or PE is used as a membrane to separate the two electrodes, and 30ml of ls-009 electrolyte is injected into each symmetrical cell. -2 Current density and 1mAh cm -2 Capacity cycling to evaluate electrochemical performance.
[0070] like Figure 7 As shown, Figure 7 Ti 0.87 XPS curves of symmetric batteries of O2@PE membrane and PE membrane after 40 cycles. 0.87 The O2@PE separator is selective for lithium ion transmission. The battery SEI component is inorganic LiF. This SEI is uniform and dense, with fast ion transmission, which is beneficial to battery cycling. On the contrary, the PE separator is not selective for lithium ion transmission. The generated organic SEI and the SEI generated by anion decomposition are porous, have no effective protection for lithium metal, and are not conducive to cycle performance.
[0071] Figure 8 Ti 0.87 Symmetrical cells of O2@PE membrane and PE membrane at 1 mA / cm 2 1mAh / cm 2 The cycle curve under the same conditions shows that the Ti 0.87 The O2@PE membrane has better cycling stability.
[0072] Example 3
[0073] Button full battery:
[0074] Assembly of Li||LFP full cell: LFP cathode (1.6 mAh cm -2) was paired with 450 μm lithium foil to assemble a full cell. The LFP-based full cell was cycled in the voltage range of 2.2 to 3.9 V with a cycle current density of 0.5C and 2C (1C = 170 mAh g -1 ). Each button cell was activated for 5 cycles at a current density of 0.1C before testing.
[0075] Assembly of Li||NCM811 full battery: NCM811 positive electrode (0.4 mAh cm -2 ) was paired with a 450 μm lithium sheet to assemble a full cell. The full cell based on NCM811 was cycled in the voltage range of 2.7 to 4.3 V with a cycle current density of 0.5C (1C = 200 mAh g -1 ). Each button cell was activated for 5 cycles at a current density of 0.1C before testing.
[0076] like Fig. 9 As shown, Fig. 9 Ti 0.87 The LFP full battery cycle performance diagram of O2@PE separator and PE separator shows that the Ti 0.87 The O2@PE membrane has better cycling stability.
[0077] Fig.10 Ti 0.87 The 811 full battery performance diagram of O2@PE membrane and PE membrane, where a is the full battery 1c cycle performance. b is the 811 full battery rate performance. It can be seen that benefiting from the uniform selective lithium ion transport characteristics in the negative charge ion transport channel, Ti 0.87 The O2@PE membrane has better cycle stability and faster ion transport.
[0078] Example 4
[0079] Soft-pack full battery: All soft-pack full batteries are assembled by semi-automated battery production lines. This includes slurry mixers, coaters, calenders, z-stackers for positive, negative and separators; ultrasonic welding of aluminum (cathode) and nickel (anode) tabs, packaging, top and side sealing, electrolyte injection, and vacuum sealing. After that, they are first charged at 0.1C for formation to form a stable solid electrolyte interface, followed by final sealing. After final sealing, long cycles are performed at 0.1C / 0.3C charge and discharge.
[0080] All soft-pack batteries used 50 μm lithium foil as the negative electrode and were injected with 2 g Ah -1 The quantitative electrolyte used is Ti 0.87 O2@PE diaphragm or PE diaphragm. All soft pack batteries were tested in a Xinwei battery cycler at a temperature of 25°C and a test voltage range of 3-4.3V.
[0081] Fig.11 Ti 0.87 Performance diagram of 811 soft pack battery with O2@PE separator and PE separator. It can be seen that the Ti 0.87 The O2@PE separator has better cycle performance when actually used in 450Wh / kg high energy density power batteries and has practical application prospects.
[0082] Therefore, the present invention adopts the above two-dimensional Ti 0.87 The modification of O2 nanosheets on the diaphragm and its application in lithium metal batteries realizes the simple and low-cost liquid phase exfoliation preparation of ultra-thin, high aspect ratio titanium oxide nanosheets containing cation defects; a simple scraping and coating method is used to modify the diaphragm to achieve ultra-thin, ultra-light, simple and large-scale modification of the lithium metal negative electrode in a natural environment; the modified layer two-dimensional materials are assembled layer by layer to construct negatively charged atomic-level ion selective transmission channels, and the ion transmission selectivity is achieved by the charge and steric effects, and the uniform transmission of lithium ions is achieved by multiple channels.
[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. Two-dimensional Ti 0.87 O 2 Modification of separators by nanosheets and their application in lithium metal batteries, It is characterized in that The layered titanate matrix is exfoliated into single-layer components: Ti 0.87 O 2 0.52 - titanium dioxide nanosheets, the titanium dioxide nanosheets, the binder polyvinylidene fluoride and the solvent NMP are uniformly mixed on the surface of the PE diaphragm and coated with a doctor blade to obtain a titanium dioxide modified composite diaphragm Ti 0.87 O 2 @PE, using Ti 0.87 O 2 @PE diaphragm, assembled into button batteries and soft pack batteries.
2. The two-dimensional Ti according to claim 1 0.87 O 2 Modification of separators by nanosheets and their application in lithium metal batteries, It is characterized in that The Ti 0.87 O 2 The specific synthesis method of the nanosheets is as follows: K 2 CO 3 , Li 2 CO 3 and anatase TiO 2 Mixing and grinding to form a uniform precursor powder; The precursor powder is calcined to obtain a layered titanate matrix K 0.8 Ti 1.73 Li 0.27 O 4 ; After cooling to room temperature, the layered titanate was protonated by stirring in 0.5 M HCl solution for 10 min-2 d; Protonated titanate H 1.07 Ti 1.73 O 4 ·H 2 O was washed with deionized water to neutral pH, collected by filtration, and dried under vacuum at room temperature; Stirring proton titanate in 0.01-0.02 M tetrabutylammonium hydroxide aqueous solution, a stable monolayer Ti 0.87 O 2 0.52 - nanosheet suspension; The obtained suspension is centrifuged at a rotation speed of 2000-5000 rpm, the supernatant is collected and freeze-dried to obtain cation defect single-layer nanosheet powder for further use.
3. The two-dimensional Ti according to claim 2 0.87 O 2 Modification of separators by nanosheets and their application in lithium metal batteries, It is characterized in that When preparing the precursor powder, K 2 CO 3 Can be replaced by Cs 2 CO 3 , K 2 CO 3 , Li 2 CO 3 and anatase TiO 2 The molar ratio is 0.4:0.14:1.
73.
4. The two-dimensional Ti according to claim 3 0.87 O 2 Modification of separators by nanosheets and their application in lithium metal batteries, It is characterized in that The calcination conditions for the precursor powder are as follows: calcination at 800-1150° C. for 10-24 h.
5. The two-dimensional Ti according to claim 4 0.87 O 2 Modification of separators by nanosheets and their application in lithium metal batteries, It is characterized in that The proton titanate is stirred in a 0.01-0.02 M tetrabutylammonium hydroxide aqueous solution for 5-14 days.
6. The two-dimensional Ti according to claim 5 0.87 O 2 Modification of separators by nanosheets and their application in lithium metal batteries, It is characterized in that The modification process of the diaphragm by the nanosheets prepared above is as follows: Adding titanium dioxide nanosheets in an amount of 10-100 mg / mL into the NMP solution, and ultrasonicating to uniformly disperse the titanium dioxide nanosheets in the NMP solvent; Add polyvinylidene fluoride binder powder to the above mixed solution and stir for 2-7 hours to obtain a slurry; After obtaining the slurry, the slurry is placed in a vacuum oven for vacuum defoaming, and an appropriate amount of the slurry is placed on the surface of the PE diaphragm for scraper coating. After coating, the diaphragm is placed in a vacuum oven and dried at 30-60°C to obtain a titanium oxide modified composite diaphragm Ti 0.87 O 2 @PE.
7. The two-dimensional Ti according to claim 6 0.87 O 2 Modification of separators by nanosheets and their application in lithium metal batteries, It is characterized in that The ultrasonic time is 30 minutes to 1 hour.
8. The two-dimensional Ti according to claim 7 0.87 O 2 Modification of separators by nanosheets and their application in lithium metal batteries, It is characterized in that The mixed solution is added into the polyvinylidene fluoride solution at a ratio of titanium dioxide:polyvinylidene fluoride=3:1-1:
4.
9. The two-dimensional Ti according to claim 8 0.87 O 2 Modification of separators by nanosheets and their application in lithium metal batteries, It is characterized in that The application method of the above-mentioned diaphragm in lithium battery is as follows: Adopt Ti 0.87 O 2 @PE diaphragm, assembled into button cells and soft-pack cells. All button cells are assembled in a glove box filled with argon gas, and all soft-pack cells are assembled in a dry room by a semi-automatic battery production line.
10. The two-dimensional Ti according to claim 9 0.87 O 2 Modification of separators by nanosheets and their application in lithium metal batteries, It is characterized in that The conditions in the glove box are: H 2 O<0.1ppm,O 2 <0.1ppm, the conditions in the dry room are: relative humidity 0.1%, dew point below -40°C, and constant temperature at 25°C.
